Session Reactions Scale-3: Initial psychometric evidence - Řiháček, Tomáš; Elliott, Robert; Owen, Jesse; Ladmanová, Michaela; Coleman, Jeremy J; Bugatti, Matteo (Psychotherapy research, 2024)
Objective: This study aimed to develop an updated brief self-report post-session measure, suitable for collecting systematic feedback on clients' session reactions in the context of measurement-based care (MBC). Method: The Session Reactions Scale-3 (SRS-3; 33 items) was developed by extending and adjusting the Revised Session Reactions Scale. In Study 1, the psychometric properties of the SRS-3 were tested on N = 242 clients. In Study 2, a brief version of the SRS-3 (SRS-3-B; 15 items) was developed using a combination of conceptual, empirical, and pragmatic criteria. In Study 3, the psychometric properties of the SRS-3-B were tested on a new sample of N = 265 clients. Results: Exploratory factor analysis supported the use of the SRS-3-B as a two-factor (helpful reactions, hindering reactions) or unidimensional (overall session evaluation) instrument. The SRS-3-B was meaningfully related to another process measure (Individual Therapy Process Questionnaire) both on the item and factor levels. Conclusions: The SRS-3-B is a reliable process measure to elicit rich and clinically meaningful feedback from clients within the MBC context and as a research instrument to assess the helpful and hindering aspects of therapy sessions.
Keywords: průzkumy a dotazníky; Psychometrics; psychoterapie; zpráva o sobě; lidé; Self Report; Psychotherapy; Humans; psychometrie; Professional-Patient Relations; Surveys and Questionnaires; vztahy mezi zdravotnickým pracovníkem a pacientem